Subjective income expectations and risks in rural India - Alok Kumar (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper analyses the pattern and determinants of income risk and expectation in rural India. It uses unique primary survey data eliciting subjective income distribution from households in twelve villages in Bihar. It finds that expected future income is significantly and positively associated with its variance. Current income is a significant predictor of expected future income and its variance. While both expected future income and its variance increase with current income, there is a significant negative association between the coefficient of variation of future income and current income, suggesting that low-income households face greater variability in their income. Upper caste households and households reliant on non-agricultural income have significantly higher expected future income and variance. Income process is highly persistent. This paper is one of the first to utilize subjective expectation data to analyse income risk in a developing country.
Keywords: D81; O1; O53; 330; subjective income distribution; expected income; household income risk; rural India